Identification of a portable determinant of cell cycle function within the carboxyl-terminal domain of the yeast CDC34 (UBC3) ubiquitin conjugating (E2) enzyme. - Kolman, C J (1992)
The ubiquitin conjugating (E2) enzyme encoded by CDC34 (UBC3) in Saccharomyces cerevisiae is required for the G1 to S transition of the cell cycle. CDC34 consists of a 170 residue amino-terminal domain that is homologous to that found in other E2s, followed by a 125 residue carboxyl-terminal domain that is specific to CDC34. We found that a truncation mutant of CDC34 which lacked the CDC34 carboxyl-terminal domain could not support the essential function of CDC34 in the cell cycle in vivo. To explore further the role of the carboxyl-terminal domain in determining the cell cycle function of CDC34, we constructed and characterized genes encoding chimeric E2s incorporating sequences from CDC34 and the related but functionally distinct E2 RAD6 (UBC2). We found that a construct encoding a chimeric RAD6-CDC34 ubiquitin conjugating enzyme, in which the 21 residue acidic carboxyl-terminal domain of RAD6 has been replaced with the 125 residue carboxyl-terminal domain of CDC34, performed the essential functions of CDC34 in vivo. This chimeric E2 also complemented the growth deficiency, UV sensitivity and sporulation deficiency of rad6 mutant strains. Deletion analysis of the CDC34 carboxyl-terminal domain in both CDC34 and the RAD6-CDC34 chimeric E2 identified a region comprising residues 171-244 of CDC34 that was sufficient to confer CDC34 function on the amino-terminal domains of CDC34 and RAD6. We suggest that this region interacts with substrates of CDC34 or with trans-acting factors (such as CDC34-specific ubiquitin protein ligases) that govern the substrate selectivity of CDC34. Congruent results demonstrating a positive role for the carboxyl-terminal domain of CDC34 in the essential function of CDC34 have also been obtained by Silver et al. (1992) and are reported in the accompanying paper.